Atrial natriuretic peptide augments the variability of sympathetic nerve activity in human heart failure - Kubo, T; Ando, S; Picton, P; Atchison, D J; Notarius, C F; Pollard, M J; Abramson, B L; Floras, J S (Journal of hypertension, 2001)
Activation of the sympathetic nervous system, decreased heart rate variability (HRV), and loss of modulation of muscle sympathetic nerve activity (MSNA) within the low frequency (LF, 0.05-0.15 Hz) range are three adverse features of advanced congestive heart failure (CHF). In healthy men, atrial natriuretic peptide (ANP) infusion attenuates reflex increases in MSNA and reduces LF components of HRV spectral power. Sympathoinhibitory actions have also been documented in CHF, but effects on the variability of MSNA and HRV have not been described. Heart rate and MSNA were recorded in 10 men (aged 39 +/- 3 years, mean +/- SE) with dilated cardiomyopathy (mean EF 20 +/- 4%) treated with angiotensin converting enzyme (ACE) inhibitors. Subjects received i.v. ANP (50 microg bolus then 50 ng/kg/min) and nitroglycerin (NTG, 8 mg/min) as a hemodynamic control. Signals at baseline, and 13-20 min into each infusion were submitted to spectral analysis. ANP had no effect on HRV, but increased MSNA LF (from 7.9 +/- 1.5 to 12.1 +/- 2.6 U2; P< 0.02) and total spectral power (from 47.9 +/- 5.4 to 61.9 +/- 6.8 U2; P < 0.05). NTG had no effect on the variability of MSNA or HRV. In CHF patients receiving ACE inhibitors, ANP (i) does not suppress HRV and (ii) enhances the modulation of MSNA, particularly within the LF range. This latter action is not observed with NTG. These findings suggest beneficial actions of exogenous ANP on neurogenic circulatory control.